Highly Skin‐Conformal Microhairy Sensor for Pulse Signal Amplification. (30th October 2014) - Pang, Changhyun; Koo, Ja Hoon; Nguyen, Amanda; Caves, Jeffrey M.; Kim, Myung‐Gil; Chortos, Alex; Kim, Kwanpyo; Wang, Paul J.; Tok, Jeffrey B.‐H.; Bao, Zhenan
<x xml:space="preserve">Abstract</x> A bioinspired microhairy sensor is developed to enable ultraconformability on nonflat surfaces and significant enhancement in the signal‐to‐noise ratio of the retrieved signals. The device shows ≈12 times increase in the signal‐to‐noise ratio in the generated capacitive signals, allowing the ultraconformal microhair pressure sensors to be capable of measuring weak pulsations of internal jugular venous pulses stemming from a human neck. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>